Childhood roots of financial literacy - Antonia Grohmann; Roy Kouwenberg; Lukas Menkhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Financial literacy predicts informed financial decisions, but what explains financial literacy? We use the concept of financial socialization and aim to represent three major agents of financial socialization: family, school and work. Thus we compile twelve relevant childhood characteristics in a new survey study and examine their relation to financial literacy, while controlling for established socio-demographic characteristics. We find in a mediation analysis that both family and school positively affect the financial literacy of adults. Moreover, financial literacy and school related variables also have a direct effect on financial behavior. This suggests that family factors and schooling work through complementary channels.
Keywords: D14; G11; I20; 330; financial literacy; financial behavior; family background; education; numeracy